2009 International Conference on Information and Communication Technologies and Development (ICTD) 2009
DOI: 10.1109/ictd.2009.5426680
|View full text |Cite
|
Sign up to set email alerts
|

Uses of mobile phones in post-conflict Liberia

Abstract: Liberia is a country emerging from years of protracted and devastating civil conflict. Left without any fixed line telephone infrastructure, it relies solely on the mobile phone for telephony. This study investigates the usage of mobile phones in this immediate post-conflict setting. In particular, we adopt the uses and gratifications approach to media research, giving focus to both instrumental and intrinsic motivations for use. Mobile phone users in both the capital city of Monrovia and in various rural area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
0
13
0
2
Order By: Relevance
“…Studies also showed that people prefer to use callback free messaging services rather than SMS because of its affordability and accessibility; this contrasts other services such as 'buzzing' that do not record missed calls on low end phones [4]. In post war Liberia, users saw their cellphones as productivity enhancers and means of connectivity to family and friends that could also be used as sources of personal security [2]. The idea of the phone as a stylish object was not considered to be important especially in rural areas [2].…”
Section: Related Workmentioning
confidence: 99%
“…Studies also showed that people prefer to use callback free messaging services rather than SMS because of its affordability and accessibility; this contrasts other services such as 'buzzing' that do not record missed calls on low end phones [4]. In post war Liberia, users saw their cellphones as productivity enhancers and means of connectivity to family and friends that could also be used as sources of personal security [2]. The idea of the phone as a stylish object was not considered to be important especially in rural areas [2].…”
Section: Related Workmentioning
confidence: 99%
“…To investigate what action possibilities health workers attribute to service robots and how these perceptions deviate between different niches, we use a mixed research approach called Q-methodology that has been widely used in various studies to uncover different thought patterns relating to the adoption and use of new technologies in different domains or settings (Baker et al, 2014;Best et al, 2010;Bouwman et al, 2012;Donner, 2004;Klaus et al, 2010;Rahim et al, 2011;Valenta & Wigger, 1997). As noted above, Q-methodology seeks to systematically explore subjectivity by measuring a person's viewpoints, opinions, attitudes, and so on (Brown, 1993).…”
Section: Methodsmentioning
confidence: 99%
“…While a few of these studies focus on the adoption, diffusion, and use of a specific ICT within a particular context, for example cellular phones for mobile banking, agricultural development, and microenterprise development. (Bankole et al 2011;Martin and Abbott 2011;Best et al 2010;Jagun et al 2008) and internet for social empowerment (Wheeler 2007;Furuholt and Kristiansen 2007), others examine ICT-related issues such as the role of intermediaries manifested as telecenters in bridging the digital divide (Sein and Furuholt 2012;Wheeler 2007;Furuholt and Kristiansen 2007). In this section, we discuss two case studies related to ICT in Africa.…”
Section: Cases Studies Of Ict Utilization In Africamentioning
confidence: 94%
“…The literature on digital divide in Africa is comprised of several detailed case studies and vignettes that focus on ICT utilization in specific countries such as Egypt (Warschauer 2003;Wheeler 2007), Ghana (Alemna and Sam 2006;EwusiMensah 2012;Fuchs and Horak 2008), Liberia (Best et al 2010), Nigeria (Jagun et al 2008;Bankole et al 2011), South Africa (Chigona andLicker 2008;Mbatha et al 2011;Fuchs and Horak 2008), Tanzania (Furuholt and Kristiansen 2007;Sein and Furuholt 2012), Tunisia (Danowitz et al 1995), and Uganda (Martin and Abbott 2011). While a few of these studies focus on the adoption, diffusion, and use of a specific ICT within a particular context, for example cellular phones for mobile banking, agricultural development, and microenterprise development.…”
Section: Cases Studies Of Ict Utilization In Africamentioning
confidence: 99%